Body mass index (BMI) of Institute of Medicine (1) entrants - Thandar, Myat (Myanmar Medical Association, 2003)
Anthropometric study on 2 batches of 1167 entrants to Yangon Institute of Medicine (1) showed that height, body weight, and BMI (mean + SD) for male ( n= 312; 17.4 + 0.6 yr) and female (n= 328; 17.4 + 0.7 yr) entrants in 5/2001 batch were 1.69 + 0.64m, 58.4+10.6kg, 20.44 + 3.66kg/m2,and 1.57+ 0.53m, 46.73 + 6.42kg, 18.9 + 2.43kg/m2respectively. In 12/2001 batch, the corresponding values for male ( n= 254; 16.6 + 0.5 yr) and female (n= 273; 16.5 + 0.6 yr) entrants were 1.58 + 0.43m, 55.06 + 11.3 kg, 19.19 + 3.42 kg/m2, and 1.53 + 0.3m, 46.55 + 8.09 kg, 18.53 + 3.03 kg/m2respectively. Out of 566 male students, 2% were obese, 13.4% overweight, 38.9% normal weight and 45.8% underweight (WHO expert consultation). In 601 female students, the corresponding data were 0.5%, 6.3%, 41.8 % and 51.4%. Thus in both sexes, underweight students outnumber those with ideal weight. The relationship between obesity and male sex was significant (p< 0.05). Height and weight of male University Entrants (16-18 yr; n= 233) studied in 1957 in Yangon (M.MyaTu & Ko Ko, 1962) were 1.63 + 0.06m and 47.11+7 kg. Over a period of four decades, the heights of male entrants remained similar while the body weight and hence BMI significantly increased (p<0.01). Since obesity globally is on the rise, monitoring of BMI of young adults should be continued.